2020
DOI: 10.1136/bmj.l6802
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of blinding on estimated treatment effects in randomised clinical trials: meta-epidemiological study

Abstract: Objectives To study the impact of blinding on estimated treatment effects, and their variation between trials; differentiating between blinding of patients, healthcare providers, and observers; detection bias and performance bias; and types of outcome (the MetaBLIND study). Design Meta-epidemiological study. Data source Cochrane Database of Systematic Reviews (2013-14). Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
193
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(204 citation statements)
references
References 33 publications
3
193
5
3
Order By: Relevance
“…14 The point estimates from all MetaBLIND main analyses showed little evidence of an impact of lack of blinding (see Appendix), except for lack of blinding of patients in trials with patient reported outcomes (ROR 0.91 [0.61-1.34]). 3 In all analyses, the 95% credible intervals were wide, consistent with no bias as well as some degree of bias in either direction. 3 Variation between results of different metaepidemiological studies is also a challenge for other aspects of trial methodology, notably the impact of inadequate concealment of allocation.…”
Section: Meta-epidemiological Studies: Rationale and Variation In Rmentioning
confidence: 56%
See 4 more Smart Citations
“…14 The point estimates from all MetaBLIND main analyses showed little evidence of an impact of lack of blinding (see Appendix), except for lack of blinding of patients in trials with patient reported outcomes (ROR 0.91 [0.61-1.34]). 3 In all analyses, the 95% credible intervals were wide, consistent with no bias as well as some degree of bias in either direction. 3 Variation between results of different metaepidemiological studies is also a challenge for other aspects of trial methodology, notably the impact of inadequate concealment of allocation.…”
Section: Meta-epidemiological Studies: Rationale and Variation In Rmentioning
confidence: 56%
“…3 In all analyses, the 95% credible intervals were wide, consistent with no bias as well as some degree of bias in either direction. 3 Variation between results of different metaepidemiological studies is also a challenge for other aspects of trial methodology, notably the impact of inadequate concealment of allocation. 7 Although such variation partly reflects imprecision, it may also imply varying degrees of systematic error or heterogeneity caused by differences of approach.…”
Section: Meta-epidemiological Studies: Rationale and Variation In Rmentioning
confidence: 56%
See 3 more Smart Citations